Outcomes of salvage liver transplant for recurrent hepatocellular carcinoma: A comparison with primary liver transplant. - Guo, Yuxin (The Korean Association of Hepato-Biliary-Pancreatic Surgery, 2023)
10.14701/ahbps.2019.23.1.1